In vitro induction of Carica papaya roots through Agrobacterium rhizogenes and 3-indolebutyric acid - Bermúdez Guzmán Manuel de Jesús; Valadez Ramírez Pedro; Buenrostro Nava, Marco Tulio; Manzo Sánchez Gilberto; Guzmán González Salvador (Revista Mexicana de Ciencias Agrícolas, 2018)
In vitro rooting of seedlings is one of the most important steps in the process of micropropagation and in C. Papaya has been one of the major limiting, having survival percentages below 50%. The present research was conducted in the laboratory of Biotechnology of the University of Colima in 2009. In order to induce an efficient root system, evaluated papaya shoots var. "Maradol" of approximately 3 cm length, inoculated with A. rhizogenes at concentrations of 1x107, 1x108 and 1x109 cells ml-1 and established on MS medium with acetosyringone (100 mM) and phloroglucinol (25 mg / L). For the experiment with auxin shoots were subcultured in MS liquid medium containing 0, 1, 2, 3, 4 and 5 μM IBA; incubated in the dark for 126 h, followed by subculture in substrate BM2 + MS mineral salts. None of the inoculated shoots with bacterial concentrations formed roots; in contrast, 100% of the treated shoots with IBA to a concentration of 3 μM formed roots. With the above demonstrates that seedlings of C. papaya may not be susceptible to strain A4 A. rhizogenes, while the use of IBA proved to be the most viable and effective option for in vitro root induction in shoots of papaya.